2019
DOI: 10.7150/ijms.32162
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms in breast cancer: a Sardinian preliminary case-control study

Abstract: Two common polymorphisms in the MTHFR gene, C677T and A1298C, are associated with reduced enzyme activity and may be associated with breast cancer susceptibility.We performed a case-control study to investigate the association between the two SNPs in the MTHFR gene and risk of breast cancer. In total, 58 breast cancer patients and 58 unaffected controls were enrolled in the study. Polymerase chain reaction/restriction fragment length polymorphism technique (PCR-RFLP) was conducted to determine the genotypes.No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
2
18
1
2
Order By: Relevance
“…Our study compared to the previous one [23], with the study groups carefully selected regarding ethnicity, greater sample size and with a control group without the auto-selection bias, showed no evidence of association between the MTHFR-rs1801133 and rs1801131 and the clinicopathological variables.…”
Section: Discussioncontrasting
confidence: 74%
“…Our study compared to the previous one [23], with the study groups carefully selected regarding ethnicity, greater sample size and with a control group without the auto-selection bias, showed no evidence of association between the MTHFR-rs1801133 and rs1801131 and the clinicopathological variables.…”
Section: Discussioncontrasting
confidence: 74%
“…The association of the biophenotype and polymorphisms highlighted the risk of presenting a more aggressive biophenotype two or three times higher in patients with the C677T and A1298C polymorphisms, respectively, suggesting an association of the polymorphisms with tumor progression. Additionally, the group also showed an association of the A1298C polymorphism with the risk of lymph node metastasis and an increased risk of developing BC in patients with polymorphic homozygous (CC) genotypes and overweight individuals [ 84 ]. However, Houghton et al did not observe a significant association between polymorphisms and BC, although relating the presence of the polymorphism to plasma folate levels has shown a strong relationship with BC.…”
Section: Mthfr C677t and A1298c Polymorphisms And Breast Cancermentioning
confidence: 99%
“…In a total of 19 studies on 15,628 subjects, it was revealed that another polymorphism, rs1801131 (A1298C), located in exon 7 of the MTHFR gene (Castiglia et al 2019), was significantly associated with BC in homozygous and allelic models, even though no significant difference was found in recessive, dominant, heterozygous, and overdominant models. Interestingly, the subgroups analysis seemed to suggest that genetic models of recessive, dominant, heterozygous, homozygous, and allelic in participants from Western Asia were significantly associated with the risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Another common SNP, A1298C (rs1801133), transforms glutamate to alanine at 429 residues and reduces enzyme activity (Wan et al 2018). Similar to C677T, there is still controversy as to the association of this mutation with BC, particularly in Asian population (Castiglia et al 2019;Kaya et al 2016).…”
Section: Introductionmentioning
confidence: 99%